GERAKAN ANTI TUAN TANAH DI DESA SAMBIREJO, KECAMATAN MANTINGAN, KABUPATEN NGAWI (STUDI KASUS TENTANG PEMBERONTAKAN PETANI DI DESA SAMBIREJO, KECAMATAN MANTINGAN, KABUPATEN NGAWI TAHUN 1963-1965) - Rosyidah, Umi (Candi, 2013)
This research is aimed to determine: (1) the background of the anti-landlord movement in Sambirejo village, Mantingan district, Ngawi in the year of 1963-1965, (2) the anti-landlord in the Sambirejo village, Mantingan district, Ngawi in the year of 1963 - 1965, (3) the impact of the anti-landlord in the Sambirejo village, Mantingan district, Ngawi in the year of 1963 - 1965 in the political, economic and social. This research used the historical method or methods of history. Historical method is the process of critically examine and analyze records and relics of the past, then reconstructed based on the data obtained so as to produce historiography. The results of this study are : (1) factor of the background occurrence of anti landlords PKI is the desire to exist in politics, PKI sight to the Indonesian revolution, land reform implementation used by the PKI, the Indonesian farmers' front existence among farmers tenants, (2) anti-landlord began planting waged between the years 1963 to 1965 to cancel the Minister of Agrarian Affairs Decree No. SK. 10/Depag/1964. Action continued through 1965 and peak dispute erupted on May 1, 1965, (3) The impact of anti-landlord movement in political field is competition between political parties, political polarization, a reaction against. Economic impact of injuries that there were 7 members BTI injuries and 10 houses belonging to tenant who is also a member of BTI vandalized and burned, Pondok Modern Gontor does not get confiscated yet by the crops due to BPPL Ngawi. Impact in the social sector, namely the emergence of anti-communist stance and coalition occurs between Pondok Modern Gontor, Masyumi, as well as other Islamic organizations and PNI to counter actions by the BTI / PKI. Keyword : movement, land, peasants, rebellion